Pengaruh Kompetensi Pedagogik Dosen Akuntansi terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Ekonomi - Sapulette, Anastasia Yunita; Kainama, Maryoni Stevanny; Manuhuttu, Silvia (Jurnal Pendidikan Ekonomi, 2023)
This study aims to analyze the influence of lecturers’ pedagogical competence on the learning motivation of students in the Economics Education Study Program who are interested in accounting. Pedagogical competence includes the ability to plan, implement, and evaluate teaching, as well as foster educational interaction with students. A quantitative approach was applied using a survey method and simple regression analysis. The sample consisted of 30 purposively selected students with a strong interest in accounting. The findings show that pedagogical competence has a positive and significant effect on students’ learning motivation. Lecturers who master the subject matter, use appropriate instructional media, and create interactive classroom environments are shown to enhance student enthusiasm and active participation. Additionally, lecturers’ ability to provide feedback and facilitate discussion strengthens students’ intrinsic motivation. These findings highlight the importance of improving pedagogical quality in higher education, particularly in accounting instruction, to support better learning outcomes.